Diaphragmatic stimulation transcutaneous electrical in vent mechanics invasive - Ferreira, Elenice Gomes (2018)
The objective of the present study was to evaluate the effect of EDET on the ventilatory weaning process and on the reduction of the time of the use of the invasive ventilatory support. This is a randomized clinical trial conducted in a private hospital in the municipality of Sarandi / PR. Sample composed of 20 patients, nine belonging to the intervention group and 11 to the control group. The application of EDET began on the first day after the evaluation of the patients, the sessions were performed until extubation, once a day and with a duration of fifteen minutes. There was a significant decrease (p = 0.0434) in the length of stay of the intervention group (mean of 8.4 days) when compared to the control group (mean of 14 days). It is concluded that EDET can reduce the patient’s time spent in mechanical ventilation.